Formic acid as a hydrogen storage material – development of homogeneous catalysts for selective hydrogen release. (27th April 2016) - Mellmann, Dörthe; Sponholz, Peter; Junge, Henrik; Beller, Matthias
Abstract : Liquid energy: formic acid is an ideal candidate for catalytic release and storage of hydrogen. Abstract : Formic acid (FA, HCO2 H) receives considerable attention as a hydrogen storage material. In this respect, hydrogenation of CO2 to FA and dehydrogenation of FA are crucial reaction steps. In the past decade, for both reactions, several molecularly defined and nanostructured catalysts have been developed and intensively studied. From 2010 onwards, this review covers recent advancements in this area using homogeneous catalysts. In addition to the development of catalysts for H2 generation, reversible H2 storage including continuous H2 production from formic acid is highlighted. Special focus is put on recent progress in non-noble metal catalysts.